2009
DOI: 10.1093/nar/gkp778
|View full text |Cite
|
Sign up to set email alerts
|

An Alu-derived intronic splicing enhancer facilitates intronic processing and modulates aberrant splicing in ATM

Abstract: We have previously reported a natural GTAA deletion within an intronic splicing processing element (ISPE) of the ataxia telangiectasia mutated (ATM) gene that disrupts a non-canonical U1 snRNP interaction and activates the excision of the upstream portion of the intron. The resulting pre-mRNA splicing intermediate is then processed to a cryptic exon, whose aberrant inclusion in the final mRNA is responsible for ataxia telangiectasia. We show here that the last 40 bases of a downstream intronic antisense Alu re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
2
18
0
3
Order By: Relevance
“…The inclusion of exon 20A was associated with a deletion of four nucleotides (GTAA) in intron 20. The authors identified a novel regulatory element within intron 20, termed “intron-splicing processing element” (ISPE), which acts as an intronic silencer of a cryptic 3′ splice site [9395]. The ISPE is recognized by the U1 snRNP, a core component of the splicing apparatus that normally binds the 5′ splice site.…”
Section: How As Can Affect the Ddrmentioning
confidence: 99%
“…The inclusion of exon 20A was associated with a deletion of four nucleotides (GTAA) in intron 20. The authors identified a novel regulatory element within intron 20, termed “intron-splicing processing element” (ISPE), which acts as an intronic silencer of a cryptic 3′ splice site [9395]. The ISPE is recognized by the U1 snRNP, a core component of the splicing apparatus that normally binds the 5′ splice site.…”
Section: How As Can Affect the Ddrmentioning
confidence: 99%
“…Splicing enhancers and silencers are 10-nucleotide-long ncRNAs that interact with SR proteins and snRNAs. They are formed by processing transcripts of Alu retroelements (Pastor et al, 2009). TEs turned out to be sources of satellites due to the capability of site-specific insertions (McGurk, Barbash, 2018) and illegitimate recombination, followed by amplification by gene conversion (Han et al, 2016).…”
Section: Other Functions Of Transposable Elementsmentioning
confidence: 99%
“…[40][41][42] Alu insertion/deletion polymorphism has been reported to be in total linkage disequilibrium with CTG repeats in myotonic dystrophy. 43 Several reports [44][45][46][47][48][49] indicate that de novo Alu insertions into intronic sequences in close proximity to the affected exon cause the downstream exon to shift from constitutive splicing to full exon skipping or alternative splicing (Table 2).…”
Section: Intronic Alterations Affect Splicing Of Capn3 Genementioning
confidence: 99%